2015
DOI: 10.18632/oncotarget.4223
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-106b inhibits osteoclastogenesis and osteolysis by targeting RANKL in giant cell tumor of bone

Abstract: Giant cell tumor (GCT) of bone consists of three major cell types: giant cells, monocytic cells, and stromal cells. From microarray analysis, we found that miR-106b was down-regulated in GCT clinical samples and further determined by fluorescence in situ hybridization. In addition, the expression of novel potential target of miR-106b, RANKL, was elevated in GCT along with previously determined targets in other tumors such as IL-8, MMP2 and TWIST. In a RANKL 3′UTR luciferase reporter assays, agomiR-106b repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Icariin has been demonstrated to play an important role in osteogenic differentiation (Cao et al, ; Wu et al, ). It has been reported that miRNAs are associated with the osteogenic differentiation, osteoclastogenesis and osteolysis (Wang et al, ; Huang et al, ; Miller et al, ). Icariin elevates miR‐21 levels and inhibits apoptosis in embryos (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Icariin has been demonstrated to play an important role in osteogenic differentiation (Cao et al, ; Wu et al, ). It has been reported that miRNAs are associated with the osteogenic differentiation, osteoclastogenesis and osteolysis (Wang et al, ; Huang et al, ; Miller et al, ). Icariin elevates miR‐21 levels and inhibits apoptosis in embryos (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of RANKL in GCT microenvironment stimulates the secretion of tumor necrosis factor-α (TNF-α) and interleukin-1β from giant cells, which in turn induces GCT stromal cell proliferation. RANKL is also an important signaling pathway which plays a vital role in osteoclastogenesis and bone resorption (22,23). Bone resorption is necessary for the establishment and promotion of tumor metastasis in the bone (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…GCTBs are characterized by the presence of numerous multinucleated osteoclastlike giant cells distributed among mononuclear stromal cells [31]. GCTBs are also characterized by extensive bone resorption, which results in regional pain and bone destruction, mostly occurring in distal femur, proximal tibia, distal radius, and sacrum [32,33]. Histologically, GCTBs can be classified into three main types, which are osteoclast-like multinucleated giant cells, monocytic round cells, and spindle-like stromal cells [34].…”
Section: Benign Bone Tumor: Giant Cell Tumormentioning
confidence: 99%